HAWAIIAN SKIRT controls size and floral organ number by modulating CUC1 and CUC2 expression - Gonzalez-Carranza, Zinnia H.; Zhang, Xuebin; Peters, Janny L.; Boltz, Veronique; Szecsi, Judit; Bendahmane, Mohammed; Roberts, Jeremy A. (Public Library of Science, 2017)
The Arabidopsis thaliana F-box gene HAWAIIAN SKIRT (HWS) affects organ growth and the timing of floral organ abscission. The loss-of-function hws-1 mutant exhibits fused sepals and increased organ size. To understand the molecular mechanisms of HWS during plant development, we mutagenized hws-1 seeds with ethylmethylsulphonate (EMS) and screened for mutations suppressing hws-1 associated phenotypes. We isolated the shs1/hws-1 (suppressor of hws-1) mutant in which hws-1 sepal fusion phenotype was suppressed. The shs1/hws-1 mutant carries a G→A nucleotide substitution in the MIR164 binding site of CUP-SHAPED COTYLEDON 1 (CUC1) mRNA. CUC1 and CUP-SHAPED COTYLEDON 2 (CUC2) transcript levels were altered in shs1, renamed cuc1-1D, and in hws-1 mutant. Genetic interaction analyses using single, double and triple mutants of cuc1-1D, cuc2-1D (a CUC2 mutant similar to cuc1-1D), and hws-1, demonstrate that HWS, CUC1 and CUC2 act together to control floral organ number. Loss of function of HWS is associated with larger petal size due to alterations in cell proliferation and mitotic growth, a role shared with the CUC1 gene.